PENGARUH BUDAYA ORGANISASI, DIKLAT DAN KOMPENSASI TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN POLEWALI MANDAR - Hamzah, Rudi (Siddiq Institute, 2022)
This study aims to test and prove empirically: (1) are the organization culture on the ferformance employee; (2) are the education and training influence on the ferformance employee; and (3 are the compensation influence on the ferformance employee; Theoretically, this research is expected to enrich and complement the knowledge in the field of human resource management so as to be useful to academics and practitioners. The type of research is explanatory research, population and sample in the study were 40 employees. The samples using total sampling technique, were analyzed by linear regression analysis with software SPSS 23. The results showed that (1) An organizational culture influence on employee performance. Value-value contained in the organizational culture of this institution will be a positive influence on employee performance improvement, the value of the most influential are the goals and expectations regarding achievement, the employee is jointly created with clear goals and expectations regarding job performance; (2) Training influential employees, through employee training programs are given the understanding of the job description and how to solve it; (3) Compensation effect on employee performance, compensation given to employees in the form of financial or non-financial contribution to the improved performance of employees, office allowances, facilities and enough salary will increase job satisfaction and will further enhance employee performance.